A Quantitative Analysis of Seasonal and Regional Forcing on the Terminus of Store Glacier, Greenland, from High Resolution Photogrammetry - Pearson, Hayden (UiT Norges arktiske universitet, 2022)
A quantitative analysis of seasonal and regional forcing on the terminus of Store Glacier, Greenland, from high resolution photogrammetry for the period between 10 May 2014 and 13 June 2014. Imagery is analyzed through ImGRAFT processing to create a detailed velocity and strain rate for the proglacial mélange and glacial terminus in order to investigate changes to glacial calving dynamics during mélange move out.